Tissue-Resident Natural Killer Cells and Their Potential Diversity - Sojka, Dorothy K. (Semin Immunol, 2014)
Conventional NK cells are well characterized in the mouse spleen and circulate in the blood. Less well described are NK cells found in organs such as the liver, thymus, and uterus. Recently we identified a tissue-resident NK (trNK) cell population in the liver, suggesting a potential diversity of trNK cells in other organs. In this review we compare and contrast the similarities and differences among the subpopulations of NK and innate lymphoid cells to the trNK cells in the liver.